2003
DOI: 10.1046/j.1466-822x.2003.00315.x
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific abundance–occupancy relationships of British mammals and birds: is it possible to explain the residual variation?

Abstract: Aim The majority of studies concerning positive interspecific abundance–occupancy relationships have used broad‐scale and microcosm data to test the occurrence and correlates of the relationship to determine which of the proposed mechanisms give rise to it. It has been argued recently that studying the residual variation about abundance–occupancy relationships is a more logical analysis and may yield faster progress in identifying the relative roles of the mechanisms. However, to date this approach has been la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
50
3
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 43 publications
8
50
3
1
Order By: Relevance
“…This is in agreement with Warren et al (2003) and He and Reed (2006) from the NBD model set a lower bound for estimates (Conlisk et al 2007, He andGaston 2007). Interestingly, while the model greatly underestimated the total abundance of southern African birds, the abundanceoccupancy slope derived from the NBD model was not significantly different from that of the 183 British birds (Holt and Gaston 2003; Table 2). To increase the accuracy of the NBD model (and probably the other OAR models), He and Reed (2006) suggested that species distributions should be mapped at spatial scales that are relevant to the life history of the study species (i.e., maps with a resolution of 0.1 to 1 km).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This is in agreement with Warren et al (2003) and He and Reed (2006) from the NBD model set a lower bound for estimates (Conlisk et al 2007, He andGaston 2007). Interestingly, while the model greatly underestimated the total abundance of southern African birds, the abundanceoccupancy slope derived from the NBD model was not significantly different from that of the 183 British birds (Holt and Gaston 2003; Table 2). To increase the accuracy of the NBD model (and probably the other OAR models), He and Reed (2006) suggested that species distributions should be mapped at spatial scales that are relevant to the life history of the study species (i.e., maps with a resolution of 0.1 to 1 km).…”
Section: Discussionsupporting
confidence: 85%
“…* P , 0.05; ** P , 0.01; *** P , 0.001. The slope of each model is compared against the slope observed by Holt and Gaston (2003) for 183 species of British birds (slope ¼ 0.66), as well as the slope from the 130 southern African species with independent abundance estimates (slope ¼ 0.27). Table 1 for key to the model abbreviations; n is the number of species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biased distribution indices have been used in studies in a wide number of ecological groups, including parasites (Poulin 1993), plants (Eycott et al 2006), invertebrates (Foggo et al 2003), fish (Blanchard et al 2005), birds (Zuckerberg et al 2009), and mammals (Holt and Gaston 2003), and it is likely that they have seriously affected the conclusions in a number of cases. For example, Winters and Wheeler (1985) and Saville and Bailey (1980) used the area fished by commercial fishermen as a measure of distribution, a measure that is likely to be equivalent to the area in which a catch rate higher than some minimum level can be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Biological Sciences Maringá, v. 27, no. 1, p. 51-55, Jan./March, 2005 metapopulacional e seleção de habitat (Holt et al, 2002). Nos períodos de maior estabilidade hidrológica (menor vazão), espera-se que os gradientes ambientais sejam os principais responsáveis pelos padrões de distribuição e de abundância nas comunidades de macroinvertebrados bentônicas em ambientes lóticos de pequeno porte (córregos e riachos), atuando, assim, de forma determinística.…”
Section: Introdução Introdução Introdução Introduçãounclassified